(untitled) (Jurnal Ipteks Terapan, 2023)
Fingerprint identification technology is the most important step in an automatic fingerprint identification system. The purpose of this paper is to introduce an approach to color image segmentation by determining the RGB and HSV values of each threshold value, calculating the distance and, converting the image to the HSV color space. The method used is color segmentation based on values ​​in RGB (red, green, blue) and HSV (Hue Saturation Value). The results obtained are that each value generated for its threshold value for rgb = 2 and hsv = 0.2 will result in an incomplete image of the hsv image as well as the rgb image, if rgb = 3 and hsv = 0.3 then the image for the hsv image the more complete and the rgb is getting smoother and more meeting. the higher the rgb and hsv values, the more unclear the rgb image will be. So it can be concluded that the threshold value of an image with hsv = 0.3 or 5 and rgb = 3 or 5 will get the rgb image smooth and dense and the hsv will be clearer and if it is entered with the value rgb = 3 and hsv = 0.4 then the hsv value clear but incomplete and the rgb image is complete and smooth but not very clear.